Perception and Past Experience 50 Years After Kanizsa's (Im)possible Experiment*. (March 2020) - Gerbino, Walter
In the revolutionary year 1968, the Institute of Psychology of the University of Trieste directed by Gaetano Kanizsa published a collective volume to celebrate the 70th birthday of Cesare L. Musatti. Kanizsa devoted the opening article to the empirical refutation of an argument developed by Musatti in Structure and experience in perceptual phenomenology . Musatti held that the debate between rationalist and empiricist theories of perception was not scientific, since a crucial experiment on the role of past experience is—in principle—impossible. Besides rejecting his mentor's argument on logical grounds, Kanizsa produced a parade of visual effects to demonstrate that in several conditions (involving object formation and camouflage, Petter's rule, phenomenal transparency, shape recognition, motion organization) actual perception violates expectations based on familiarity with specific objects. The empirical refutation of expectations based on past experience was recurrent in Kanizsa's subsequent production and represents a lively topic of current perceptual science, though Musatti's smile is still here.